Three-dimensional surface topography - Stout, K. J. (Penton Press, 2000)
This fully illustrated text explains the basic measurement techniques, describes the commercially available instruments and provides an overview of the current perception of 3-D topography analysis in the academic world and industry, and the commonly used 3-D parameters and plots for the characterizing and visualizing 3-D surface topography. It also includes new sections providing full treatment of surface characterization, filtering technology and engineered surfaces, as well as a fully updated bibliography.